2009
DOI: 10.1007/s10800-008-9759-0
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine derivatives as inhibitors of the corrosion of mild steel in 3.9 M HCl

Abstract: The inhibitory action of two piperazine derivatives, 1-benzyl piperazine (P1) and bis(1-benzylpiperazine) thiuram disulfide (P2) on the corrosion of mild steel in 3.9 M HCl at different concentrations has been investigated in the temperature domain 298-333 K. Both weight loss measurements and potentiodynamic polarization methods showed that P2 was the best inhibitor and that its inhibition efficiency increased with concentration to a value [92% at 10 -3 M. Potentiodynamic polarization studies clearly revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The creation of a protective barrier over the metal surface was verified by SEM and FTIR. 146 Ousslim et al (2009) evaluated the mild steel corrosion inhibition efficiency of two piperazine derivatives in an aggressive solution of 3.9 M HCl through the PDP and WL methods. 147 Mohamed (2006) investigated quinine as a corrosion inhibitor for low carbon steel in HCl solution using the PDP and EIS methodologies, reporting an inhibition efficacy of 96% at a concentration of 0.48 mM.…”
Section: Green Corrosion Inhibition By Selection: Replacement Of Toxi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The creation of a protective barrier over the metal surface was verified by SEM and FTIR. 146 Ousslim et al (2009) evaluated the mild steel corrosion inhibition efficiency of two piperazine derivatives in an aggressive solution of 3.9 M HCl through the PDP and WL methods. 147 Mohamed (2006) investigated quinine as a corrosion inhibitor for low carbon steel in HCl solution using the PDP and EIS methodologies, reporting an inhibition efficacy of 96% at a concentration of 0.48 mM.…”
Section: Green Corrosion Inhibition By Selection: Replacement Of Toxi...mentioning
confidence: 99%
“…146 Ousslim et al (2009) evaluated the mild steel corrosion inhibition efficiency of two piperazine derivatives in an aggressive solution of 3.9 M HCl through the PDP and WL methods. 147 Mohamed (2006) investigated quinine as a corrosion inhibitor for low carbon steel in HCl solution using the PDP and EIS methodologies, reporting an inhibition efficacy of 96% at a concentration of 0.48 mM. 148 Rajeswarie et al (2013) investigated the inhibition activity of three Schiff bases on cast iron using aqueous solutions of NaCl, NaOH, NH 4 Cl, and HCl.…”
Section: Green Corrosion Inhibition By Selection: Replacement Of Toxi...mentioning
confidence: 99%
“…Thus, through interaction between these charged molecules, the inhibitor molecules deposited onto metal [52][53][54]. Sometimes both these mechanisms are also reported where nature of inhibitors reported as cathodic, anodic, or mixed type [55][56][57]. The inhibitor normally deposited as a monolayer above the metal considered as Langmuir adsorption model [58][59][60].…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…These compounds are also used in vulcanizing synthetic rubber. 15 As per corrosion studies, Ousslim et al 16 evaluated the mitigation of mild steel corrosion in 3.9 M HCl using bis(1-benzylpiperazine)thiuram disulfide and achieved an inhibition efficiency of 91.2% at 10 –3 M. In a similar report, the team assessed the inhibitory performance of three piperidine compounds including bis(4-benzylpiperidine)thiuram disulfide (P2) for mild steel degradation in 5.5 M H 3 PO 4 . At elevated concentration, P2 behaved as a predominant cathodic inhibitor and inhibited corrosion to the tune of 96% at 1 mM concentration at 298 K. 17 The inhibitive effect of three disulfides flavoring agents (PPD, DBD, and DAD) on copper in 0.5 M H 2 SO 4 was investigated via electrochemical and computational techniques by Tan et al 18 The study reported excellent inhibition efficacies of 98.5% (PPD), 92.10% (DBD), and 91.50% (DAD) with a maximum concentration of 5 mM at 298 K. Recently, an extensive study was conducted on the corrosion protection of cobalt in alkaline solution using two disulfide compounds, 2,2-dibenzamidodiphenyl disulfide and 3,3-dithiodipropionic acid.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are also used in vulcanizing synthetic rubber . As per corrosion studies, Ousslim et al evaluated the mitigation of mild steel corrosion in 3.9 M HCl using bis­(1-benzylpiperazine)­thiuram disulfide and achieved an inhibition efficiency of 91.2% at 10 –3 M. In a similar report, the team assessed the inhibitory performance of three piperidine compounds including bis­(4-benzylpiperidine)­thiuram disulfide (P2) for mild steel degradation in 5.5 M H 3 PO 4 . At elevated concentration, P2 behaved as a predominant cathodic inhibitor and inhibited corrosion to the tune of 96% at 1 mM concentration at 298 K .…”
Section: Introductionmentioning
confidence: 99%